Monooxygenase, a Novel Beta-Cypermethrin Degrading Enzyme from Streptomyces sp - Chen, Shaohua; Lin, Qingsheng; Xiao, Ying; Deng, Yinyue; Chang, Changqing; Zhong, Guohua; Hu, Meiying; Zhang, Lian-Hui (PloS one, 2013)
The widely used insecticide beta-cypermethrin has become a public concern because of its environmental contamination and toxic effects on mammals. In this study, a novel beta-cypermethrin degrading enzyme designated as CMO was purified to apparent homogeneity from a Streptomyces sp. isolate capable of utilizing beta-cypermethrin as a growth substrate. The native enzyme showed a monomeric structure with a molecular mass of 41 kDa and pI of 5.4. The enzyme exhibited the maximal activity at pH 7.5 and 30°C. It was fairly stable in the pH range from 6.5-8.5 and at temperatures below 10°C. The enzyme activity was significantly stimulated by Fe(2+), but strongly inhibited by Ag(+), Al(3+), and Cu(2+). The enzyme catalyzed the degradation of beta-cypermethrin to form five products via hydroxylation and diaryl cleavage. A novel beta-cypermethrin detoxification pathway was proposed based on analysis of these products. The purified enzyme was identified as a monooxygenase by matrix-assisted laser desorption/ionization time-of-flight/time-of-flight mass spectrometry analysis (MALDI-TOF-MS) and N-terminal protein sequencing. Given that all the characterized pyrethroid-degrading enzymes are the members of hydrolase family, CMO represents the first pyrethroid-degrading monooxygenase identified from environmental microorganisms. Taken together, our findings depict a novel pyrethroid degradation mechanism and indicate that the purified enzyme may be a promising candidate for detoxification of beta-cypermethrin and environmental protection.